Interactions of thought and action in Old English poetry - Ponirakis, Eleni (2017)
The Anglo-Saxon mind has been the focus of much critical attention in recent years; however, most criticism has considered the mind in isolation the better to understand Anglo-Saxon psychology and philosophy. My thesis examines the mind from a different perspective and considers it as an agent of action which does not perform in isolation, but in tandem with the body. This perspective reveals a number of significant patterns which are present across different genres of poetry and prose and which seem to have their basis in classically influenced Christian thought. A study of Anglo-Saxon Christian texts shows that the interrelation between mental and physical acts was central to early medieval Christian thought. To give an example, Ælfric writes, tihtað eower mod to gecnyrdnysse godra weorca, þæt ge mid geðylde godne wæstm to Godes handa gebringon (direct your minds to eagerness of good works, that you with patience bring good fruits to God’s hands); for Ælfric the kingdom of heaven is obtained through good work and good work is the product of the mind. Mental and physical acts are connected and the one relies upon the other. Tropes include an ideal of balance; opposition of movement to stasis, where stasis is equated with wisdom and God, and movement is associated with emotion and moving away from God; the importance of mental control and the danger of uncontrolled thought or emotion. I have analysed three Old English poems in the light of this interplay: The Battle of Maldon, The Seafarer and Juliana. Maldon shows a detailed pattern of balance between mental and physical acts and a clear pattern of danger signalled by any examples of excess. Right action here is a product of right thinking and not innate heroism and this separates Maldon from both Beowulf and Brunanburh, heralding a new kind of Christianised hero. The poet of The Seafarer has used the distribution of mental and physical acts to reveal the true identity of the narrator. It becomes apparent on analysis that the speaker in the first 66 lines of the poem performs no physical acts himself, despite an abundance of violent physical action in the poem. Agency is given to the elements of nature and the thoughts and emotions of the speaker who submits to action but never performs it. This is a clue to the true identity of the speaker in the first part of the poem. In Juliana the interaction most closely resembles the figures abundant in Ælfric and Boethius as the saint battles for control of her mind and body, suggesting that Cynewulf was writing from a similar perspective. This analysis has offered new insights into longstanding cruces such as the significance of ofermod in Maldon, the mysterious sylf-cunnige in Seafarer 35, and the absence of emotion for the eponymous heroine of Juliana. Furthermore, the presence of these patterns across the corpus brings into question the current division of Old English prose and poetry into ‘classical’ and ‘vernacular’ traditions.